Biodelignification of oil palm trunk- optimization - Haziatun, Mohd Fazi (2012)
Biodelignification is a process to remove lignin from the lignocellulosic materials to obtain celluloses.Hence this study is introduced to study the optimum value of the most affected parameters to the biodelignification process in order to maximize the removal of the lignin.Those parameters are temperature pH, moisture content and also fungi to medium ratio.As for this research,a local type of fungi, Pleurotus ostreatus or commercially known as ‘Oyster Mushrooms’,were used as an agent of delignification and the raw material chosen are oil palm trunk wastes.In order to optimize conditions for production of lignocellulolytic enzymes by the oyster mushroom,a Response Surface Methodology(RSM) based experiment was designed by using Design Expert software.In this research,30 runs of experiment were done.After obtaining the experimental design table,the experimental procedures were preceded and the values of the parameters were set according to the table at respective value.After that,the lignin content was analyzed by using Klason Lignin Method.With this method,the lignin content can be determined for various values of parameters. Then,the results obtained were analyzed again by using Design Expert software.At the end of this research,the optimum conditions obtained for the lignin degradation of oil palm trunk fiber are with temperature of 25 °C, pH value of 7.0,moisture content of 0.21 ml and fungi to medium ratio of 2.5 with the amount of predicted lignin degraded is 15.37%.Finally,the conformational test was done with the optimum conditions obtained and the error between the actual and predicted value is 18.7%. However,for better results, the center point in RSM should be tested before designing the experiment.